Copper-Functionalized Metal–Organic Framework as Catalyst for Oxidant-Controlled Partial Oxidation of Cyclohexene - Pannapat Chotmongkolsap (2019)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim Microwave irradiation is exploited for the facile, one-step functionalization of Cu(acac)2 to –NH2 pendant groups of MIL-53(Al)-NH2, a metal–organic framework material, under mild reaction conditions and a short reaction time. PXRD, XPS, XAS, and EPR spectroscopy are used to investigate the structure and chemical nature of the copper species on the framework. The copper center exists in the +2 oxidation state with a square-planar geometry and NO3 coordination environment. The copper complex is anchored to the framework by imine bond formation. This copper-functionalized MIL-53(Al)-NH2 or MIL-53[Cu] is employed in the catalytic oxidation of olefins using molecular oxygen (O2) or tert-butyl hydroperoxide (TBHP) as the oxidant. The chemoselectivities of the oxidation products depend on the type of oxidant and substrate. When O2 is used as the oxidant and isobutyraldehyde as the co-oxidant in the oxidation of cyclohexene with MIL-53[Cu], cyclohexene oxide is the major product. However, when TBHP is employed as the oxidant, 2-cyclohexen-1-one is the major product. Furthermore, the catalyst can be reused at least three times without a significant loss in activity.